Nodular typhlocolitis, heterakiasis, and mesenchymal neoplasia in a ring-necked pheasant (Phasianus colchicus) with immunohistochemical characterization of visceral metastases. (July 2017) - Himmel, Lauren; Cianciolo, Rachel
A 9-y-old, male ring-necked pheasant ( Phasianus colchicus ) was autopsied following euthanasia because of acute distress, recumbency, and dyspnea. The bird had experienced a protracted period of neuromuscular disease localized to the left sciatic nerve. Gross and histologic examination of the large intestine revealed intramural nodules predominantly comprised of atypical, whorling spindle cells with small cores of granulomatous inflammation centered on cross-sections of immature adult nematodes. The body structures of these metazoan organisms and clinical disease manifestation are consistent with Heterakis isolonche infection. Nodular spindle cell proliferations without granulomatous inflammation or intralesional nematodes were also found throughout the liver and lungs, suggesting metastasis from the intestine. Immunohistochemical staining of the hepatic and pulmonary tumor tissue with vimentin and S100 suggests a neurofibroblastic origin.